A high-reflectivity tpo waterproofing membrane for photovoltaics and method of making the same
Patent Information
- Application Number
- CN202611398446.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]为此,本发明提供一种光伏用高反光度TPO防水卷材及其制备方法,用以克服现有技术中防水卷材难以同时兼顾高反射耐久性、双面光伏组件背面受光增益以及防水卷材受机械穿刺部位密封可靠性低的问题
[0016]与现有技术相比,本发明的有益效果在于,本发明通过设置自上而下依次复合的高反射耐候层、过渡粘结层、中间功能层、自愈合密封层和底面增强层,使防水卷材不再仅作为普通防水材料使用,而是形成适用于光伏屋面的复合功能卷材。各功能层分别承担反射耐候、层间连接、隔热支撑、穿刺密封和基层增强作用,能够更好地适应光伏屋面长期暴晒、温度循环、支架安装和雨水冲刷等复杂工况。
Smart Images

Figure CN122876745A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building-integrated photovoltaic (BIPV) waterproofing materials, and more particularly to a high-reflectivity TPO waterproof membrane for photovoltaic applications and its preparation method. Background Technology
[0002] With the increasing scale of building-integrated photovoltaics (BIPV), commercial and industrial rooftop PV, and bifacial PV module applications, roof waterproofing membranes are no longer limited to ordinary building waterproofing functions. They are increasingly required to possess multiple functions, including waterproofing protection, enhanced reflectivity, weather resistance and anti-aging properties, adaptability to bracket installation, and stability in later operation and maintenance. In existing PV roofs, if ordinary dark-colored TPO waterproofing membranes are used, the surface absorbs more solar radiation, easily leading to increased temperature on the back of the PV modules, thus affecting module power generation efficiency. If a white coating is used to increase reflectivity, the coating is prone to chalking, peeling, and reflectivity degradation under long-term UV exposure, temperature cycling, and rain erosion. Furthermore, PV bracket fasteners often need to press or puncture the waterproofing membrane during installation; if the puncture site cannot form a reliable seal, it can easily become a weak point for roof leakage. Therefore, it is necessary to provide a high-reflectivity TPO waterproof membrane suitable for photovoltaic roofs, which can improve the roof's reflectivity through a high-reflectivity weather-resistant layer, form diffuse reflection suitable for the back of bifacial photovoltaic modules through surface micro-nano structures, and seal the puncture sites of photovoltaic bracket fasteners through a self-healing sealing layer, thereby simultaneously improving the waterproof reliability, power generation gain, and long-term stability of photovoltaic roofs.
[0003] Chinese Patent Publication No. CN117922135A discloses a polyolefin waterproof membrane and its preparation and application. It can be seen that the polyolefin waterproof membrane mainly forms a three-layer structure through an intermediate adhesive layer and TPO material layers disposed on both sides of the intermediate adhesive layer. By incorporating components such as polyisobutylene, terpene resin, C5 hydrogenated resin, and butyl rubber into the intermediate adhesive layer, the intermediate adhesive layer possesses certain creep and self-healing properties, thereby automatically repairing penetrated and damaged areas during mechanical fixing construction, reducing the risk of leakage at mechanical fixing locations.
[0004] However, this structure still has the following shortcomings: On the one hand, it mainly focuses on the self-healing repair problem after the waterproof membrane is penetrated during mechanical fixing construction, and does not set up a high-reflection and weather-resistant structure for photovoltaic roofs, especially for bifacial photovoltaic modules, making it difficult to improve the roof's solar reflection utilization effect through the membrane itself; on the other hand, the structure does not design a diffuse reflection structure on the surface of the membrane, nor does it improve the bulk reflection capability of the membrane through multi-scale gradation of high-refractive-index hollow reflective particles and hollow scattering particles, making it difficult to simultaneously meet the requirements of enhanced light reception on the back of photovoltaic modules, heat dissipation of modules, and long-term weather-resistant reflection. Summary of the Invention
[0005] To address this, the present invention provides a high-reflectivity TPO waterproof membrane for photovoltaic applications and its preparation method, thereby overcoming the problems in the prior art where waterproof membranes cannot simultaneously achieve high reflectivity and durability, light gain on the back side of bifacial photovoltaic modules, and low sealing reliability at mechanically punctured locations.
[0006] To achieve the above objectives, the present invention provides a high-reflectivity TPO waterproof membrane for photovoltaic applications, comprising: The layers are sequentially composited from top to bottom: a high-reflectivity weather-resistant layer, a transition adhesive layer, an intermediate functional layer, a self-healing sealing layer, and a bottom reinforcement layer. The high-reflectivity weather-resistant layer is used to reflect and scatter sunlight incident on the photovoltaic module installation area, and includes a TPO matrix and high-refractive-index hollow reflective particles and hollow scattering particles dispersed in the TPO matrix. The transition bonding layer is used to connect the high-reflectivity weather-resistant layer and the intermediate functional layer and to relieve interlayer thermal stress; The intermediate functional layer, which provides mechanical support and thermal insulation, includes a TPO matrix and hollow fillers dispersed in the TPO matrix; The self-healing sealing layer is disposed between the intermediate functional layer and the bottom reinforcement layer, and is used to provide flow sealing for roll material ruptures caused by external mechanical punctures. The self-healing sealing layer includes a TPO matrix, liquid polyisobutylene, and tackifying resin. The bottom reinforcement layer is used to connect with the target attachment base layer.
[0007] Further, the high-reflectivity weather-resistant layer comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of high-refractive-index hollow reflective particles, 5 to 15 parts of hollow scattering particles, 0.5 to 2 parts of ultraviolet absorber, 0.3 to 1 part of antioxidant, and 0.2 to 0.5 parts of light stabilizer. The high-refractive-index hollow reflective particles are titanium dioxide hollow particles or titanium dioxide-coated hollow particles, and the hollow scattering particles are hollow glass microspheres.
[0008] Furthermore, the high-refractive-index hollow reflective particles have a particle size D50 of 2 μm to 8 μm and a hollowness greater than 85%. The particle size D50 of the hollow scattering particles is 10μm to 50μm; The high-refractive-index hollow reflective particles fill the packing gaps between the hollow scattering particles to form a multi-scale graded reflective structure within the high-reflectivity weather-resistant layer.
[0009] Furthermore, a micro-nano rough structure is formed on the side of the high-reflectivity weather-resistant layer away from the transition adhesive layer. The micro-nano rough structure includes micron-sized protrusions and nano-sized pits formed between or on the surface of the micron-sized protrusions. The diameter of the micron-sized protrusion is 5μm to 20μm, the height is 3μm to 10μm, and the depth of the nano-sized pit is 0.5μm to 2μm.
[0010] Furthermore, the self-healing sealing layer comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of liquid polyisobutylene, 5 to 15 parts of tackifying resin, and 3 to 8 parts of microcapsule wax. The liquid polyisobutylene has a molecular weight of 1000-3000, and the microcapsule wax has a phase transition temperature of 50℃-70℃.
[0011] Furthermore, the intermediate functional layer comprises, by weight, 100 parts of TPO matrix, 20 to 40 parts of hollow filler, 10 to 20 parts of inorganic filler, and 3 to 8 parts of processing aid; The hollow filler is hollow glass microspheres, the inorganic filler is calcium carbonate, and a closed-cell structure is formed in the intermediate functional layer to reduce the thermal conductivity of the waterproof membrane and improve its mechanical support performance. The transition adhesive layer comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of maleic anhydride grafted polyolefin, and 5 to 15 parts of tackifying resin. The bottom reinforcing layer comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of sheet-like reflective filler, and 5 to 10 parts of tackifying resin; The sheet-like reflective filler is dispersed in the TPO matrix of the bottom reinforcing layer, and the sheet-like reflective filler is titanium dioxide coated mica sheet.
[0012] On the other hand, the present invention also provides a preparation method, comprising: Step S1: Obtain the raw materials for the high-reflectivity weather-resistant layer, the transition adhesive layer, the intermediate functional layer, the self-healing sealing layer, and the bottom reinforcement layer, respectively. Step S2: The high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material, and bottom reinforcement layer material are melted and plasticized respectively. Step S3: The melted and plasticized materials are compositely formed by a multi-layer co-extrusion device to form a five-layer composite roll material from top to bottom, including a high-reflectivity weather-resistant layer, a transition bonding layer, an intermediate functional layer, a self-healing sealing layer and a bottom reinforcement layer. Step S4: Perform surface structure treatment on the side of the high-reflectivity weather-resistant layer away from the transition bonding layer to form a micro-nano rough structure on the surface of the high-reflectivity weather-resistant layer for diffuse reflection and hydrophobic self-cleaning. Step S5 involves cooling, shaping, traction, edge trimming, and winding of the five-layer composite roll with the micro-nano rough structure to obtain the photovoltaic high-reflectivity TPO waterproof roll.
[0013] Further, in step S4, the surface structure treatment performed on the side of the high-reflectivity weather-resistant layer away from the transition adhesive layer includes: The surface of the high-reflectivity weather-resistant layer is subjected to plasma treatment, embossing treatment, and hydrophobic treatment in sequence; The plasma treatment uses a mixed atmosphere of oxygen and argon, with a treatment power of 200W to 500W and a treatment time of 2 to 5 minutes. The embossing process uses an embossing roller with a hydrophobic microstructure on its surface, with an embossing temperature of 80℃~120℃ and an embossing pressure of 2MPa~5MPa, to form a micro-nano rough structure including micron-level protrusions and nano-level pits on the surface of the high-reflectivity weather-resistant layer. The hydrophobic treatment involves spraying or impregnating the micro / nano rough structure with a fluorosilane solution to form a hydrophobic surface layer on the surface of the micro / nano rough structure.
[0014] Further, in step S3, the melt-plasticized high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material and bottom reinforcement layer material are compositely formed by a five-layer co-extrusion distributor; The extrusion temperature of each layer of material is set to 180℃~240℃, the cooling roller temperature is 30℃~50℃, and the traction speed is 5m / min~20m / min; Adjust the extrusion amount of each extrusion mechanism so that the thickness of the high-reflectivity weather-resistant layer is 0.5mm to 1.0mm, the thickness of the transition bonding layer is 0.2mm to 0.4mm, the thickness of the intermediate functional layer is 1.0mm to 2.0mm, the thickness of the self-healing sealing layer is 0.3mm to 0.6mm, and the thickness of the bottom reinforcing layer is 0.5mm to 1.0mm.
[0015] Furthermore, the width of at least one side of the self-healing sealing layer is smaller than that of the bottom reinforcement layer, so that the lower surface of at least a portion of the intermediate functional layer on the corresponding side is connected to the upper surface of the bottom reinforcement layer; In the plasma treatment, the volume ratio of oxygen to argon is 1:4 to 1:1.
[0016] Compared with existing technologies, the beneficial effects of this invention are that, by setting up a high-reflectivity weather-resistant layer, a transition bonding layer, an intermediate functional layer, a self-healing sealing layer, and a bottom reinforcement layer in a sequentially composite manner from top to bottom, the waterproof membrane is no longer used merely as an ordinary waterproof material, but rather forms a composite functional membrane suitable for photovoltaic roofs. Each functional layer undertakes the functions of reflectivity and weather resistance, interlayer bonding, thermal insulation support, puncture sealing, and base layer reinforcement, respectively, and can better adapt to the complex working conditions of photovoltaic roofs such as long-term exposure to sunlight, temperature cycling, bracket installation, and rain erosion.
[0017] Furthermore, this invention incorporates high-refractive-index hollow reflective particles and hollow scattering particles within the high-reflectivity weather-resistant layer, creating a multi-scale reflection and scattering structure within the roll material. Compared to simply coating the roll material surface with a white coating, the reflective function of this invention primarily originates from the high-reflectivity weather-resistant layer itself. This helps reduce the risk of rapid decline in reflectivity due to surface coating chalking and peeling, thereby improving the reflectivity stability of the roll material during long-term outdoor use.
[0018] Furthermore, this invention enhances the roof's ability to reflect sunlight through a high-reflectivity weather-resistant layer, reducing the absorption of solar radiation by the roofing material and decreasing heat accumulation on the back of the photovoltaic modules, thus improving the power generation stability of the photovoltaic modules. Simultaneously, the micro-nano rough structure on the surface of the high-reflectivity weather-resistant layer enables more uniform diffuse reflection of incident light, dispersing the reflected light in multiple directions. This improves the light reception range on the back of the bifacial photovoltaic modules and reduces glare caused by strong specular reflection.
[0019] Furthermore, this invention incorporates a self-healing sealing layer. When the photovoltaic bracket fasteners puncture the waterproof membrane, the self-healing sealing layer viscoelastically flows along the wall of the puncture hole, sealing the gaps around the fasteners and the puncture hole, thereby reducing the risk of leakage channels forming at the photovoltaic bracket installation location. Thus, this invention not only meets the photovoltaic roof's need for enhanced reflection efficiency but also ensures reliable waterproof sealing after bracket installation, overcoming the limitation of existing waterproof membranes having only one function.
[0020] Furthermore, the transition bonding layer of this invention can alleviate interlayer stress concentration caused by differences in material composition and thermal expansion and contraction between adjacent functional layers, reducing the risk of delamination, bulging, or cracking under long-term temperature cycling; the hollow filler in the intermediate functional layer can reduce the density of the roll material and improve the thermal insulation effect while ensuring mechanical support performance; the bottom reinforcement layer can improve the connection stability between the roll material and the building substrate. Through the above structural combination, this invention can simultaneously achieve high reflectivity, diffuse reflection, self-cleaning, thermal insulation and lightweight properties, puncture self-healing sealing, and long-term waterproof protection, making it particularly suitable for building-integrated photovoltaics (BIPV) roofs, commercial and industrial roof PV systems, and bifacial PV module installation scenarios. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the overall layered structure of the high-reflectivity TPO waterproof membrane for photovoltaic applications of the present invention; Figure 2 This is a partially enlarged structural diagram of the high-reflectivity weather-resistant layer of the present invention; Figure 3 This is a schematic diagram illustrating how the self-healing sealing layer of the present invention seals the puncture hole of the photovoltaic bracket. Figure 4 This is a schematic diagram of the preparation method of the high reflectivity TPO waterproof membrane for photovoltaic applications according to the present invention.
[0022] In the diagram: 10. Waterproof membrane; 11. High-reflectivity weather-resistant layer; 12. Transition adhesive layer; 13. Intermediate functional layer; 14. Self-healing sealing layer; 15. Bottom reinforcement layer; 20. Photovoltaic bracket fastener; 21. Puncture hole; 22. Sealing area; 111. High-refractive-index hollow reflective particles; 112. Hollow scattering particles; 113. Micro-nano rough structure. Detailed Implementation
[0023] To make the objectives and advantages of the present invention clearer, the present invention will be further described below with reference to embodiments; it should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention.
[0024] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.
[0025] It should be noted that in the description of this invention, the terms "upper", "lower", "left", "right", "inner", "outer", etc., which indicate directions or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings. This is only for the convenience of description and is not intended to indicate or imply that the device or element must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation of this invention.
[0026] This embodiment of the high-reflectivity TPO waterproof membrane for photovoltaics is mainly used in building-integrated photovoltaic (BIPV) roofs, commercial and industrial rooftop photovoltaic systems, and bifacial photovoltaic module installation scenarios. It can be used as a waterproofing material for the roof beneath the photovoltaic modules. Through a combination of high reflectivity, diffuse reflection, thermal insulation support, and self-healing sealing structures, it improves the waterproofing reliability of the photovoltaic roof and the light reception effect on the back of the photovoltaic modules. The waterproof membrane 10 in this embodiment is not a single-function ordinary roof waterproof membrane, but rather a composite of a high-reflectivity weather-resistant structure, interlayer bonding structure, thermal insulation support structure, self-healing sealing structure, and bottom reinforcement structure. This allows it to meet the waterproofing requirements of building roofs while adapting to long-term installation of photovoltaic modules, puncture of bracket fasteners, solar radiation, and outdoor temperature cycling. Please see Figures 1 to 3 As shown, where, Figure 1 This is a schematic diagram of the overall layered structure of the high-reflectivity TPO waterproof membrane for photovoltaic applications of the present invention; Figure 2 This is a partially enlarged structural diagram of the high-reflectivity weather-resistant layer of the present invention; Figure 3 This is a schematic diagram illustrating the sealing of the photovoltaic bracket puncture hole by the self-healing sealing layer of the present invention; the high-reflectivity TPO waterproof membrane 10 for photovoltaic applications in this embodiment includes: The high-reflectivity weather-resistant layer 11, transition adhesive layer 12, intermediate functional layer 13, self-healing sealing layer 14, and bottom reinforcement layer 15 are sequentially composited from top to bottom.
[0027] Specifically, the high-reflectivity weather-resistant layer 11 is located on the uppermost side of the waterproof membrane 10, and is used to directly withstand solar radiation, ultraviolet radiation and external environmental effects, and to improve the ability of the waterproof membrane 10 to reflect and scatter sunlight.
[0028] The transition bonding layer 12 is disposed between the high-reflectivity weather-resistant layer 11 and the intermediate functional layer 13 to enhance the bonding stability between adjacent layers and alleviate the interlayer stress caused by temperature changes between different material layers.
[0029] The intermediate functional layer 13 is disposed below the transition adhesive layer 12 and is used to provide mechanical support, thermal insulation and lightweight effect for the waterproof membrane 10.
[0030] The self-healing sealing layer 14 is disposed between the intermediate functional layer 13 and the bottom reinforcing layer 15, and is used to perform flow sealing around the puncture hole 21 after external mechanical puncture, such as when the photovoltaic bracket fastener 20 punctures the waterproof membrane 10 and forms a puncture hole 21.
[0031] The bottom reinforcement layer 15 is located at the bottommost side of the waterproof membrane 10 and is used to improve the connection stability between the waterproof membrane 10 and the building substrate.
[0032] In this embodiment, the waterproof membrane 10 utilizes a five-layer composite structure to achieve its composite functions. The high-reflectivity, weather-resistant layer 11 enhances the reflectivity of the photovoltaic roof; the transition bonding layer 12 ensures interlayer bonding; the intermediate functional layer 13 improves support and insulation performance; the self-healing sealing layer 14 reduces the risk of leakage at bracket puncture sites; and the bottom reinforcement layer 15 enhances the installation stability of the membrane's bottom. Through the combined structure of these layers, the waterproof membrane 10 can simultaneously meet the photovoltaic roof's requirements for waterproofing, reflection, insulation, installation sealing, and long-term weather resistance.
[0033] Specifically, the high-reflectivity weather-resistant layer 11 is disposed on the uppermost side of the waterproof membrane 10, serving as a surface structure that directly withstands solar radiation, ultraviolet radiation, rainwater erosion, and the effects of the external air environment.
[0034] The high-reflectivity weather-resistant layer 11 includes a TPO matrix and high-refractive-index hollow reflective particles 111 and hollow scattering particles 112 dispersed in the TPO matrix. Through the combination of the high-refractive-index hollow reflective particles 111 and hollow scattering particles 112, sunlight incident on the high-reflectivity weather-resistant layer 11 can undergo multiple reflections and scatterings at different particle interfaces, thereby improving the reflectivity of the waterproof membrane 10 to sunlight, reducing the absorption of solar radiation by the waterproof membrane 10, and helping to reduce heat accumulation in the back area of the photovoltaic module.
[0035] The transition bonding layer 12 is disposed between the high-reflectivity weather-resistant layer 11 and the intermediate functional layer 13. Since the high-reflectivity weather-resistant layer 11 contains particulate materials to improve reflectivity, while the intermediate functional layer 13 is mainly used to provide support and thermal insulation, the two differ in material composition and thermal deformation characteristics. Therefore, by setting the transition bonding layer 12, the interlayer bonding stability between the high-reflectivity weather-resistant layer 11 and the intermediate functional layer 13 can be enhanced. When the waterproof membrane 10 is subjected to long-term diurnal temperature variations, seasonal temperature cycles, and the thermal radiation of photovoltaic modules, it can alleviate the thermal stress concentration between adjacent layers and reduce the risk of interlayer peeling, bulging, or cracking.
[0036] The intermediate functional layer 13 is disposed below the transition bonding layer 12 and serves as one of the main support layers of the waterproof membrane 10, improving the overall strength and dimensional stability of the waterproof membrane 10. Hollow fillers can be dispersed within the intermediate functional layer 13, forming a lightweight filling structure within the TPO matrix. This allows the intermediate functional layer 13 to provide both mechanical support and thermal insulation. Consequently, the waterproof membrane 10 can reduce roof load in photovoltaic roofs and decrease the transfer of external heat to the building substrate, making it suitable for applications such as commercial and industrial rooftop photovoltaics, existing building roof renovations, and building-integrated photovoltaics (BIPV).
[0037] The self-healing sealing layer 14 is disposed between the intermediate functional layer 13 and the bottom reinforcing layer 15, serving as a functional layer for puncture sealing in the waterproof membrane 10. The self-healing sealing layer 14 may include a TPO matrix, liquid polyisobutylene, and tackifying resin, exhibiting viscoelastic flowability. When the photovoltaic bracket fastener 20 punctures the waterproof membrane 10, forming a puncture hole 21, the self-healing sealing layer 14 becomes fluid under heat, flowing locally around the puncture hole 21 and adhering to the hole wall, thereby sealing the gap between the photovoltaic bracket fastener 20 and the waterproof membrane 10 and reducing the risk of rainwater seeping downwards along the puncture hole 21. Furthermore, in the event of mechanical cracks or other cracks or perforations in the waterproof membrane 10, heating allows the self-healing sealing layer 14 to flow to the crack or perforation location and fill and seal the opening. Because it fills through internal flow, it avoids the problem of low interlayer bonding strength associated with external repairs.
[0038] The bottom reinforcement layer 15 is disposed on the bottommost side of the waterproof membrane 10. It is used to cooperate with the building roof base or bonding base to improve the connection stability of the waterproof membrane 10 after it is laid. The bottom reinforcement layer 15 can enhance the deformation resistance and installation adaptability of the bottom of the waterproof membrane 10, so that the waterproof membrane 10 is not prone to warping, slippage or detachment due to thermal expansion and contraction of the base layer, local stress or construction disturbance during long-term use.
[0039] It is understood that in this embodiment, the high-reflectivity weather-resistant layer 11, the transition bonding layer 12, the intermediate functional layer 13, the self-healing sealing layer 14, and the bottom reinforcement layer 15 together constitute a multifunctional composite waterproof structure suitable for photovoltaic roofs, enabling the waterproof membrane 10 to simultaneously possess functions such as reflectivity enhancement, heat insulation support, puncture sealing, and base layer connection.
[0040] Please continue reading. Figure 2 As shown, the high-reflectivity weather-resistant layer 11 is the surface structure of the waterproof membrane 10 that provides the main reflective function. It contains high-refractive-index hollow reflective particles 111 and hollow scattering particles 112. Both the high-refractive-index hollow reflective particles 111 and hollow scattering particles 112 are dispersed within the TPO matrix of the high-reflectivity weather-resistant layer 11, ensuring that the high-reflectivity weather-resistant layer 11 does not rely solely on a surface coating for reflection, but rather forms a stable reflection and scattering structure through the particle interfaces within the layer.
[0041] Specifically, the high-refractive-index hollow reflective particles 111 can be hollow titanium dioxide particles or hollow particles coated with titanium dioxide, which can form a refractive index difference interface between the outer wall of the particles and the TPO matrix. When sunlight enters the high-reflectivity weather-resistant layer 11, some of the light can be reflected at the outer wall interface of the high-refractive-index hollow reflective particles 111 and inside the hollow structure, thereby increasing the proportion of light reflected outward and reducing the amount of light that continues to pass into the waterproof membrane 10 and is absorbed by the membrane.
[0042] The hollow scattering particles 112 can be hollow glass microspheres, with a particle size larger than the high-refractive-index hollow reflective particles 111. The hollow scattering particles 112 can act as scattering centers within the high-reflectivity weather-resistant layer 11, causing light entering the high-reflectivity weather-resistant layer 11 to change direction during propagation and extending the propagation path of the light within the high-reflectivity weather-resistant layer 11. Therefore, light can undergo multiple reflections and scatterings between the high-refractive-index hollow reflective particles 111 and the hollow scattering particles 112, improving the overall reflectivity of the high-reflectivity weather-resistant layer 11.
[0043] Preferably, the particle size D50 of the high-refractive-index hollow reflective particles 111 is 2 μm to 8 μm, and the particle size D50 of the hollow scattering particles 112 is 10 μm to 50 μm. Because the high-refractive-index hollow reflective particles 111 have a smaller particle size, they can fill the gaps between the hollow scattering particles 112, thereby forming a multi-scale gradation structure within the high-reflectivity weather-resistant layer 11. This multi-scale gradation structure increases the number of interfaces between the particles and the TPO matrix, allowing incident light to have more opportunities for reflection and scattering within the high-reflectivity weather-resistant layer 11.
[0044] Furthermore, a micro / nano rough structure 113 is provided on the surface of the high-reflectivity weather-resistant layer 11 away from the transition adhesive layer 12. The micro / nano rough structure 113 may include micron-sized protrusions, tiny pits, or a rough surface formed by embossing or plasma treatment. By providing the micro / nano rough structure 113, sunlight irradiated onto the surface of the high-reflectivity weather-resistant layer 11 can be transformed from unidirectional reflection to multidirectional diffuse reflection, thereby increasing the reception range of reflected light on the back side of the bifacial photovoltaic module and reducing glare problems caused by specular reflection.
[0045] Furthermore, the micro-nano rough structure 113 can also improve the hydrophobic self-cleaning performance of the high-reflectivity weather-resistant layer 11 surface. When rainwater falls on the surface of the high-reflectivity weather-resistant layer 11, it is easier to form rolling water droplets and carry away the dust or particulate matter attached to the surface, thereby reducing the impact of long-term dust cover on the reflectivity of the high-reflectivity weather-resistant layer 11. Thus, the high-refractive-index hollow reflective particles 111, hollow scattering particles 112, and micro-nano rough structure 113 work together to enable the high-reflectivity weather-resistant layer 11 to simultaneously possess bulk high reflectivity, surface diffuse reflectivity, and hydrophobic self-cleaning functions.
[0046] like Figure 3 As shown, during the installation of photovoltaic modules, the photovoltaic bracket fasteners 20 typically need to tighten and secure the waterproof membrane 10. In some installation methods, the photovoltaic bracket fasteners 20 may puncture the waterproof membrane 10, forming a puncture hole 21 within the waterproof membrane 10. If an effective seal cannot be formed around the puncture hole 21, rainwater can easily seep downwards along the gap between the photovoltaic bracket fasteners 20 and the waterproof membrane 10, making this location a weak point in the photovoltaic roof waterproofing system.
[0047] In this embodiment, the self-healing sealing layer 14 is disposed between the intermediate functional layer 13 and the bottom reinforcement layer 15. When the photovoltaic bracket fastener 20 passes through the high-reflectivity weather-resistant layer 11, the transition adhesive layer 12, the intermediate functional layer 13 from top to bottom and further through the self-healing sealing layer 14, the self-healing sealing layer 14, after being punctured and squeezed, can undergo local deformation and viscoelastic flow around the puncture hole 21. Because the self-healing sealing layer 14 has a certain degree of softness, adhesion, and flow sealing ability, it can adhere to the hole wall of the puncture hole 21 and cover the outer periphery of the photovoltaic bracket fastener 20.
[0048] Specifically, after the photovoltaic bracket fastener 20 punctures the waterproof membrane 10, the viscoelastic material in the self-healing sealing layer 14 can backfill and adhere along the inner wall of the puncture hole 21, filling any tiny gaps that might have existed between the photovoltaic bracket fastener 20 and the waterproof membrane 10, thereby forming a sealing area 22 around the puncture hole 21. The sealing area 22 can block rainwater from continuing to penetrate downwards along the puncture hole 21, improving the waterproof reliability of the photovoltaic bracket installation location.
[0049] Furthermore, since the self-healing sealing layer 14 is not located on the outermost surface of the waterproof membrane 10, but rather inside the waterproof membrane 10, it is less susceptible to direct exposure to ultraviolet radiation, rainwater erosion, and external abrasion while achieving the puncture sealing function. This reduces the risk of the self-healing sealing material failing due to long-term external environmental effects, ensuring that it maintains a relatively stable sealing effect even after the photovoltaic bracket fastener 20 has been punctured.
[0050] Therefore, this embodiment, by setting a self-healing sealing layer 14 inside the waterproof membrane 10, enables the waterproof membrane 10 to not only achieve enhanced reflection efficiency of the photovoltaic roof through the high-reflectivity weather-resistant layer 11, but also to actively seal the puncture holes 21 during the installation of the photovoltaic bracket. Compared with the method of relying solely on the elastic recovery of the ordinary TPO layer, this embodiment can more reliably seal the leakage channels around the photovoltaic bracket fasteners 20, thereby improving the long-term waterproof stability of the photovoltaic roof system.
[0051] Please see Figure 4As shown, this is a schematic diagram of the preparation method of the high-reflectivity TPO waterproof membrane for photovoltaic applications according to the present invention; this embodiment also provides a method for preparing the high-reflectivity TPO waterproof membrane 10 for photovoltaic applications, including: Step S1: Obtain the raw materials for the high-reflectivity weather-resistant layer, the transition adhesive layer, the intermediate functional layer, the self-healing sealing layer, and the bottom reinforcement layer, respectively. Step S2: The high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material, and bottom reinforcement layer material are melted and plasticized respectively. Step S3: The melted and plasticized materials are compositely formed by a multi-layer co-extrusion device to form a five-layer composite roll material from top to bottom, including a high-reflectivity weather-resistant layer, a transition bonding layer, an intermediate functional layer, a self-healing sealing layer and a bottom reinforcement layer. Step S4: Perform surface structure treatment on the side of the high-reflectivity weather-resistant layer away from the transition bonding layer to form a micro-nano rough structure on the surface of the high-reflectivity weather-resistant layer for diffuse reflection and hydrophobic self-cleaning. Step S5 involves cooling, shaping, traction, edge trimming, and winding of the five-layer composite roll with the micro-nano rough structure to obtain the photovoltaic high-reflectivity TPO waterproof roll.
[0052] Specifically, in step S1, a high-reflectivity weather-resistant layer material, a transition adhesive layer material, an intermediate functional layer material, a self-healing sealing layer material, and a bottom reinforcement layer material are prepared respectively.
[0053] In this embodiment, the preparation process of the high-reflectivity weather-resistant layer material is as follows: Specifically, the high-reflectivity weather-resistant layer material comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of high-refractive-index hollow reflective particles, 5 to 15 parts of hollow scattering particles, 0.5 to 2 parts of ultraviolet absorber, 0.3 to 1 part of antioxidant, and 0.2 to 0.5 parts of light stabilizer. The high-refractive-index hollow reflective particles are titanium dioxide hollow particles or titanium dioxide-coated hollow particles, and the hollow scattering particles are hollow glass microspheres. During preparation, the high-refractive-index hollow reflective particles and hollow scattering particles are weighed according to the above-mentioned weight proportions and premixed to form a composite high-reflection filler. Then, the TPO matrix, composite high-reflection filler, ultraviolet absorber, antioxidant and light stabilizer are mixed and granulated to obtain a high-reflection weather-resistant layer material.
[0054] The transition adhesive layer material comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of maleic anhydride-grafted polyolefin, and 5 to 15 parts of tackifying resin. During preparation, the TPO matrix, maleic anhydride-grafted polyolefin, and tackifying resin are weighed according to the above weight proportions, and the components are mixed evenly and then granulated to obtain the transition adhesive layer material.
[0055] The intermediate functional layer material comprises, by weight, 100 parts of TPO matrix, 20-40 parts of hollow filler, 10-20 parts of inorganic filler, and 3-8 parts of processing aid; wherein the hollow filler is hollow glass microspheres, and the inorganic filler is calcium carbonate; in preparation, the TPO matrix, hollow glass microspheres, calcium carbonate, and processing aid are weighed according to the above-mentioned weight parts, the calcium carbonate and processing aid are premixed with at least a portion of the TPO matrix, the hollow glass microspheres are added and mixed at low speed, and the mixed components are granulated to obtain the intermediate functional layer material.
[0056] The self-healing sealing layer material comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of liquid polyisobutylene, 5 to 15 parts of tackifying resin, and 3 to 8 parts of microcapsule wax. During preparation, the TPO matrix, liquid polyisobutylene, tackifying resin, and microcapsule wax are weighed according to the above weight proportions. First, the TPO matrix and tackifying resin are mixed, then the liquid polyisobutylene is added and mixed. After the liquid polyisobutylene is uniformly dispersed, the microcapsule wax is added and mixed under low shear to obtain the self-healing sealing layer material.
[0057] The bottom reinforcement layer material comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of sheet-like reflective filler, and 5 to 10 parts of tackifying resin; wherein the sheet-like reflective filler is titanium dioxide coated mica sheet; during preparation, the TPO matrix, titanium dioxide coated mica sheet, and tackifying resin are weighed according to the above weight parts, and the components are mixed evenly and then granulated to obtain the bottom reinforcement layer material.
[0058] In step S2, the high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material, and bottom reinforcement layer material obtained in step S1 are melt-plasticized separately, so that each layer material gradually changes from a solid or semi-solid state to a fluid molten state. Each layer material is melt-plasticized separately to prevent the different functional layer materials from mixing before entering the composite molding process, and to form a uniformly composed and stable molten material, providing the corresponding molten raw material for the subsequent multi-layer co-extrusion composite molding in step S3. In step S3, the melt-plasticized high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material, and bottom reinforcement layer material are respectively conveyed to a five-layer co-extrusion distributor, converged through the composite flow channel, and extruded through the co-extrusion die, so that each layer material sequentially forms a high-reflectivity weather-resistant layer 11, a transition adhesive layer 12, an intermediate functional layer 13, a self-healing sealing layer 14, and a bottom reinforcement layer 15 from top to bottom.
[0059] In step S3, the high-reflectivity weather-resistant layer molten material, transition bonding layer molten material, intermediate functional layer molten material, self-healing sealing layer molten material, and bottom reinforcement layer molten material obtained in step S2 are respectively conveyed to the five-layer co-extrusion distributor. Each layer of molten material enters the co-extrusion die through the corresponding flow channel and is composite extruded, so that it forms a high-reflectivity weather-resistant layer 11, a transition bonding layer 12, an intermediate functional layer 13, a self-healing sealing layer 14, and a bottom reinforcement layer 15 from top to bottom, thereby obtaining a continuous five-layer composite roll material.
[0060] During the co-extrusion process, the extrusion temperature of each layer of material is controlled within the range of 180℃ to 240℃; among them, the extrusion temperature of the high-reflectivity weather-resistant layer material is preferably 195℃ to 215℃, the extrusion temperature of the transition bonding layer material is preferably 185℃ to 205℃, the extrusion temperature of the intermediate functional layer material is preferably 190℃ to 210℃, the extrusion temperature of the self-healing sealing layer material is preferably 180℃ to 195℃, and the extrusion temperature of the bottom reinforcing layer material is preferably 190℃ to 210℃, so that the molten material of each layer maintains stable flow in the co-extrusion channel and forms a continuous composite interface at the exit of the co-extrusion die.
[0061] During the co-extrusion molding process, the thickness of each functional layer is controlled by adjusting the amount of molten material supplied to each layer, so that the thickness of the high-reflectivity weather-resistant layer 11 is 0.5mm to 1.0mm, the thickness of the transition bonding layer 12 is 0.2mm to 0.4mm, the thickness of the intermediate functional layer 13 is 1.0mm to 2.0mm, the thickness of the self-healing sealing layer 14 is 0.3mm to 0.6mm, and the thickness of the bottom reinforcing layer 15 is 0.5mm to 1.0mm.
[0062] Furthermore, by controlling the lateral width of the flow channel corresponding to the self-healing sealing layer 14, at least one side of the self-healing sealing layer 14 is recessed inward relative to the corresponding side of the bottom reinforcement layer 15, thereby directly connecting the lower surface of at least a portion of the intermediate functional layer 13 on the corresponding side to the upper surface of the bottom reinforcement layer 15. In this way, the highly viscoelastic self-healing sealing layer 14 does not extend to at least one edge of the roll material, thereby improving the structural stability of the roll material edge area and the reliability of subsequent overlap construction.
[0063] Step S4 includes: First, the surface of the high-reflectivity weather-resistant layer 11 away from the transition bonding layer 12 is subjected to plasma treatment. The plasma treatment uses a mixed atmosphere of oxygen and argon, wherein the volume ratio of oxygen to argon is 1:4 to 1:1. The working pressure in the treatment chamber is controlled at 30Pa to 150Pa. The plasma is generated by excitation with a radio frequency power supply at a frequency of 13.56MHz, a treatment power of 200W to 500W, and a treatment time of 2min to 5min. During the treatment, oxygen plasma is used to activate the TPO substrate surface of the high-reflectivity weather-resistant layer 11, and argon plasma is used to improve the uniformity of the treatment, so that the surface of the high-reflectivity weather-resistant layer 11 forms an activated surface suitable for subsequent embossing and hydrophobic treatment.
[0064] Subsequently, the plasma-treated high-reflectivity weather-resistant layer 11 is embossed using an embossing roller with a preset microstructure on its surface, so that micron-level protrusions and nano-level pits located between or on the surface of the high-reflectivity weather-resistant layer 11 are formed on its surface. In this embodiment, the preset microstructure can be a surface biomimetic structure, such as the shape structure of the microstructure of the lotus leaf surface, or other microstructures with hydrophobic function, which will not be elaborated here.
[0065] After embossing, a fluorosilane solution is uniformly sprayed onto the surface of the micro-nano rough structure 113, allowing the fluorosilane to adhere to the surface of the plasma-activated high-reflectivity weather-resistant layer 11. After drying, a hydrophobic surface layer is formed. Thus, the multi-scale gradation of the reflective structure inside the high-reflectivity weather-resistant layer 11, together with the micro-nano rough structure 113 on the surface, forms both bulk reflection and diffuse surface reflection. Furthermore, the low surface energy surface layer formed by the fluorosilane improves the hydrophobic self-cleaning properties of the roll material surface.
[0066] After the surface structure treatment is completed, the reflectivity of the treated roll material is tested, and the obtained reflectivity is compared with a preset reflectivity. When the obtained reflectivity is lower than the preset reflectivity, the amount of high-refractive-index hollow reflective particles added to the high-reflectivity weather-resistant layer material in the subsequent preparation process is increased to improve the reflectivity of the resulting waterproof roll material. In this embodiment, the preset reflectivity is set to 85%.
[0067] In step S5, the five-layer composite roll material after surface structure treatment is cooled and shaped by passing through cooling rollers in sequence, and the preset traction speed is maintained by the traction device to keep the structure of each layer of the roll material continuous and flat during the cooling process; then the irregular edges on both sides of the roll material are cut off and rolled up according to the preset length to obtain photovoltaic high reflectivity TPO waterproof roll material 10. Example 1
[0068] This embodiment uses an optimized ratio of each component to prepare a high-reflectivity TPO waterproof membrane 10 for photovoltaic applications.
[0069] The high-reflectivity weather-resistant layer 11 comprises, by weight, 100 parts of TPO matrix, 22 parts of high-refractive-index hollow reflective particles, 10 parts of hollow scattering particles, 1 part of ultraviolet absorber, 0.6 parts of antioxidant, and 0.3 parts of light stabilizer; wherein, the high-refractive-index hollow reflective particles are titanium dioxide hollow particles with a particle size D50 of 5 μm and a hollowness of 90%, and the hollow scattering particles are hollow glass microspheres with a particle size D50 of 25 μm.
[0070] The transition adhesive layer 12 comprises, by weight, 100 parts of TPO matrix, 15 parts of maleic anhydride-grafted polyolefin, and 10 parts of tackifying resin.
[0071] The intermediate functional layer 13 comprises, by weight, 100 parts of TPO matrix, 30 parts of hollow glass microspheres, 15 parts of calcium carbonate, and 5 parts of processing aids.
[0072] The self-healing sealing layer 14 comprises, by weight, 100 parts of TPO matrix, 22 parts of liquid polyisobutylene, 10 parts of tackifying resin and 5 parts of microcapsule wax, wherein the molecular weight of liquid polyisobutylene is 2000 and the phase transition temperature of microcapsule wax is 60℃.
[0073] The bottom reinforcing layer 15 comprises, by weight, 100 parts of TPO matrix, 18 parts of titanium dioxide-coated mica sheets, and 8 parts of tackifying resin.
[0074] The above five layers of materials are prepared according to step S1, and melt-plasticized according to step S2. The extrusion temperature of the high-reflectivity weather-resistant layer material is 205°C, the extrusion temperature of the transition bonding layer material is 195°C, the extrusion temperature of the intermediate functional layer material is 200°C, the extrusion temperature of the self-healing sealing layer material is 190°C, and the extrusion temperature of the bottom reinforcing layer material is 200°C.
[0075] Five melts are compounded and formed using a five-layer co-extrusion distributor, resulting in a high-reflectivity weather-resistant layer 11 with a thickness of 0.8 mm, a transition bonding layer 12 with a thickness of 0.3 mm, an intermediate functional layer 13 with a thickness of 1.5 mm, a self-healing sealing layer 14 with a thickness of 0.45 mm, and a bottom reinforcement layer 15 with a thickness of 0.8 mm. The self-healing sealing layer 14 is recessed inwards by 30 mm on each side relative to the bottom reinforcement layer 15 along the width of the roll, creating edge connection areas on both sides of the roll where the intermediate functional layer 13 and the bottom reinforcement layer 15 are directly connected.
[0076] The surface of the co-extruded high-reflectivity weather-resistant layer 11 was subjected to plasma treatment, in which the volume ratio of oxygen to argon was 1:2, the treatment power was 350W, and the treatment time was 3min. Subsequently, an embossing roller with a lotus leaf-like microstructure was used for embossing, with an embossing temperature of 100℃ and an embossing pressure of 3.5MPa, so that the surface of the high-reflectivity weather-resistant layer 11 formed micron-sized protrusions with an average diameter of about 10μm and a height of about 6μm, as well as nano-sized pits with a depth of about 1μm. Then, a 2% fluorosilane solution was uniformly sprayed onto its surface and dried.
[0077] Finally, the roll is cooled and shaped by a cooling roller at a temperature of 40°C, and then pulled at a speed of 12 m / min. After edge trimming and winding, the photovoltaic high-reflectivity TPO waterproof roll 10 of this embodiment is obtained. Example 2
[0078] This embodiment uses the smaller end ratio within the range of each component.
[0079] The high-reflectivity weather-resistant layer 11 comprises, by weight, 100 parts of TPO matrix, 15 parts of high-refractive-index hollow reflective particles, 5 parts of hollow scattering particles, 0.5 parts of ultraviolet absorber, 0.3 parts of antioxidant, and 0.2 parts of light stabilizer. The high-refractive-index hollow reflective particles have a particle size D50 of 2 μm and a hollowness greater than 85%, while the hollow scattering particles have a particle size D50 of 10 μm.
[0080] The transition bonding layer 12 comprises, by weight, 100 parts of TPO matrix, 10 parts of maleic anhydride-grafted polyolefin, and 5 parts of tackifying resin; the intermediate functional layer 13 comprises, by weight, 100 parts of TPO matrix, 20 parts of hollow glass microspheres, 10 parts of calcium carbonate, and 3 parts of processing aid; the self-healing sealing layer 14 comprises, by weight, 100 parts of TPO matrix, 15 parts of liquid polyisobutylene, 5 parts of tackifying resin, and 3 parts of microcapsule wax, wherein the molecular weight of liquid polyisobutylene is 1000 and the phase transition temperature of microcapsule wax is 50℃; and the bottom reinforcing layer 15 comprises, by weight, 100 parts of TPO matrix, 10 parts of titanium dioxide-coated mica sheets, and 5 parts of tackifying resin.
[0081] The five-layer material was prepared and co-extruded according to the method described in Example 1, wherein the thicknesses of the high-reflectivity weather-resistant layer 11, the transition adhesive layer 12, the intermediate functional layer 13, the self-healing sealing layer 14, and the bottom reinforcing layer 15 are 0.5 mm, 0.2 mm, 1.0 mm, 0.3 mm, and 0.5 mm, respectively.
[0082] During the surface treatment process, the volume ratio of oxygen to argon was 1:4, the plasma treatment power was 200W, and the treatment time was 2 minutes. The embossing temperature was 80℃, and the embossing pressure was 2MPa, which caused micron-sized protrusions with a diameter of approximately 5μm and a height of approximately 3μm and nano-sized pits with a depth of approximately 0.5μm to form on the surface of the high-reflectivity weather-resistant layer 11. Subsequently, a 1% (w / w) fluorosilane solution was used for surface spraying treatment. The cooling roller temperature was 30℃, and the traction speed was 5m / min. After cooling, edge trimming, and winding, the waterproof membrane of this embodiment was obtained. Example 3
[0083] This embodiment uses the larger end ratio within the range of each component.
[0084] The high-reflectivity weather-resistant layer 11 comprises, by weight, 100 parts of TPO matrix, 30 parts of high-refractive-index hollow reflective particles, 15 parts of hollow scattering particles, 2 parts of ultraviolet absorber, 1 part of antioxidant, and 0.5 parts of light stabilizer. The high-refractive-index hollow reflective particles have a particle size D50 of 8 μm and a hollowness greater than 85%, while the hollow scattering particles have a particle size D50 of 50 μm.
[0085] The transition bonding layer 12 comprises, by weight, 100 parts of TPO matrix, 25 parts of maleic anhydride-grafted polyolefin, and 15 parts of tackifying resin; the intermediate functional layer 13 comprises, by weight, 100 parts of TPO matrix, 40 parts of hollow glass microspheres, 20 parts of calcium carbonate, and 8 parts of processing aids; the self-healing sealing layer 14 comprises, by weight, 100 parts of TPO matrix, 30 parts of liquid polyisobutylene, 15 parts of tackifying resin, and 8 parts of microcapsule wax, wherein the molecular weight of liquid polyisobutylene is 3000 and the phase transition temperature of microcapsule wax is 70℃; and the bottom reinforcing layer 15 comprises, by weight, 100 parts of TPO matrix, 25 parts of titanium dioxide-coated mica sheets, and 10 parts of tackifying resin.
[0086] The five-layer material was prepared and co-extruded according to the method described in Example 1. The thicknesses of the high-reflectivity weather-resistant layer 11, the transition bonding layer 12, the intermediate functional layer 13, the self-healing sealing layer 14, and the bottom reinforcing layer 15 are 1.0 mm, 0.4 mm, 2.0 mm, 0.6 mm, and 1.0 mm, respectively.
[0087] During the surface treatment process, the volume ratio of oxygen to argon was 1:1, the plasma treatment power was 500W, and the treatment time was 5 minutes. The embossing temperature was 120℃, and the embossing pressure was 5MPa, which formed micron-sized protrusions with a diameter of approximately 20μm and a height of approximately 10μm, and nano-sized pits with a depth of approximately 2μm on the surface of the high-reflectivity weather-resistant layer 11. Subsequently, a 3% (w / w) fluorosilane solution was used for surface spraying treatment. The cooling roller temperature was 50℃, and the traction speed was 20m / min. After cooling, edge trimming, and winding, the waterproof membrane of this embodiment was obtained.
[0088] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the high-reflectivity weather-resistant layer 11 in Example 1 is replaced with a common TPO surface layer of the same thickness. This common TPO surface layer does not contain high-refractive-index hollow reflective particles or hollow scattering particles, and its surface is not treated with micro / nano roughening. The structure of the remaining layers, the thickness of each layer, and the preparation conditions are the same as in Example 1. This comparative example is used to compare the effects of the multi-scale gradation of reflective structures within the high-reflectivity weather-resistant layer and the micro / nano roughening structure on the solar reflectivity of the roll material.
[0089] The ordinary TPO surface layer comprises, by weight, 100 parts of TPO matrix, 2 parts of UV absorber, 1 part of antioxidant and 0.5 parts of light stabilizer.
[0090] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the self-healing sealing layer 14, composed of liquid polyisobutylene, tackifying resin, and microcapsule wax, is not used. Instead, a conventional TPO layer with the same thickness as the self-healing sealing layer 14 is used at corresponding positions to maintain a relatively consistent total thickness for each sample. The remaining structure, material composition, and preparation conditions are the same as in Example 1. This comparative example is used to compare the effect of the self-healing sealing layer 14 on the waterproof sealing performance at the puncture sites of photovoltaic bracket fasteners.
[0091] Comparative Example 3 Comparative Example 3 uses the waterproof membrane of Comparative Example 1 as the main body, and an aluminum foil reflective layer is laminated on the upper surface of the waterproof membrane of Comparative Example 1 to give it a high surface reflectivity in its initial state. Comparative Example 3 does not include a bulk reflection structure composed of high-refractive-index hollow reflective particles and hollow scattering particles, nor does it include the micro / nano rough structure 113. The remaining sample dimensions are consistent with those of Example 1. This comparative example is used to compare the reflection stability of the high-reflectivity weather-resistant layer of this invention with that of a traditional surface metal reflective layer under long-term use conditions.
[0092] To verify the technical effects of the above embodiments, solar reflectance performance tests and waterproof performance tests after mechanical puncture were conducted on Examples 1-3 and Comparative Examples 1-3, respectively. The test results are shown in Table 1 below.
[0093] In the solar reflectance performance test, each sample is cut to the same size and placed in the same temperature and humidity environment for a preset time. The reflectance of the sample facing the sunlight is then measured. At least five different locations are selected for each sample, and the average value is taken to obtain the initial reflectance of each sample. Furthermore, each sample can be subjected to ultraviolet aging and thermal cycling treatment, and the reflectance can be measured again to evaluate the reflectance retention capability of different reflective structures in long-term outdoor environments.
[0094] In the mechanical puncture waterproof performance test, photovoltaic bracket fasteners 20 of the same specification were used to vertically penetrate each sample. With the fasteners in their installed state, the water tightness of the puncture site was tested. Under a preset water pressure for a preset time, the back of the sample and the area around the fasteners were observed for water droplets, continuous seepage, or leakage marks. After the test, the fasteners were removed, and the sample was placed at 60°C for a preset time to conduct another water tightness test to evaluate the backfill sealing ability of the self-healing sealing layer 14 to the puncture hole 21.
[0095] The test results of each embodiment and comparative example can be recorded according to the following indicators: initial solar reflectance, solar reflectance after aging, reflectance retention rate, waterproof performance under fastener puncture condition, and waterproof performance after fastener is pulled out and treated with self-healing.
[0096] The above experiments can verify the technical effects of the high-reflectivity weather-resistant layer 11, the self-healing sealing layer 14, and the multi-layer composite structure. In particular, Examples 1-3 form a bulk multi-scale reflective structure through high-refractive-index hollow reflective particles and hollow scattering particles, and form multi-directional diffuse reflection through the micro-nano rough structure 113, thus improving the ability of the roll material to reflect and utilize sunlight. The liquid polyisobutylene, tackifying resin, and microcapsule wax in the self-healing sealing layer 14 can undergo local viscoelastic flow around the puncture hole 21 after the photovoltaic bracket fastener 20 is punctured, and fill the gap, thereby reducing the possibility of forming a continuous leakage channel at the puncture site.
[0097] Table 1. Comprehensive comparison results between the examples and comparative examples
[0098]
[0099]
[0100] Performance evaluation and results analysis Regarding solar reflectivity, the initial total solar reflectivity of Examples 1-3 were 91.8%, 86.9%, and 93.4%, respectively, all significantly higher than the 63.8% of Comparative Example 1, which used a common TPO surface layer. Example 3 exhibited the highest reflectivity, indicating that with the increased use of high-refractive-index hollow reflective particles and hollow scattering particles, the bulk multi-scale reflective structure further enhances the reflectivity of the roll material to sunlight. While Comparative Example 3 achieved a relatively high initial reflectivity of 89.7% through its aluminum foil reflective layer, its diffuse reflection accounted for only 24.5% of the total reflection, significantly lower than the 79.8%-86.1% of Examples 1-3. This suggests that the combination of bulk reflection and surface micro / nano roughness structure in this invention is more conducive to forming multi-directional diffuse reflection, reducing glare caused by single specular reflection.
[0101] Regarding weather resistance, after 1000 hours of comprehensive aging, the reflectivity retention rates of Examples 1-3 remained above 94.9%, with Example 1 reaching 96.8%. The reflectivity retention rate of Comparative Example 3 decreased to 83.2%, and localized wrinkling and edge delamination of the aluminum foil occurred after thermal cycling. These results indicate that the reflectivity of this invention is primarily provided by the particle reflective structure within the high-reflectivity weather-resistant layer, exhibiting better reflectivity and structural stability under ultraviolet irradiation and thermal cycling conditions compared to the surface reflectivity of the outer aluminum foil.
[0102] Regarding surface hydrophobicity and thermal insulation properties, the water contact angles of Examples 1-3 were 145°-154°, significantly higher than the 92° of Comparative Example 1 (without micro / nano rough structures and hydrophobic treatment) and the 83° of Comparative Example 3 (aluminum foil surface). This indicates that the plasma-activated, embossed micro / nano rough structures and the fluorosilane hydrophobic treatment can synergistically improve the surface's hydrophobic self-cleaning ability. The thermal conductivity of Examples 1-3 was 0.129-0.161 W / (m·K), generally remaining at a low level, with Example 3 being the lowest, indicating that the hollow glass microspheres in the intermediate functional layer can provide effective thermal insulation.
[0103] Regarding interlayer bonding performance, the interlayer peel strength of Examples 1-3 was 33.2-38.6 N / 25mm, maintaining stable interlayer bonding; Comparative Example 3 showed only 21.6 N / 25mm and edge delamination occurred after thermal cycling, indicating that the direct composite aluminum foil reflective layer is more prone to interfacial stress concentration under temperature cycling conditions. This invention connects the high-reflectivity weather-resistant layer and the intermediate functional layer through a transition adhesive layer, which can alleviate the differences in thermal deformation between different functional layers and is beneficial for maintaining long-term interlayer stability.
[0104] Regarding puncture and self-healing waterproof performance, Examples 1-3 showed no leakage after being punctured and kept in the installed state, and were kept under 0.30 MPa water pressure for 2 hours. After the fastener was removed and left at room temperature for 24 hours, Examples 1 and 2 showed only slight or small amounts of seepage, while Example 3 showed no continuous leakage. After treatment at 60°C for 2 hours, all examples returned to a leak-free state. In contrast, Comparative Example 2, which used a common TPO layer instead of a self-healing sealing layer, showed leakage after fastener puncture for 18 minutes, and continued to leak after fastener removal and after treatment at 60°C. This indicates that the self-healing sealing layer composed of liquid polyisobutylene, tackifying resin, and microcapsule wax can undergo viscoelastic flow around the puncture hole and further promote backfilling under heating conditions, thereby significantly improving the sealing reliability of the puncture site.
[0105] In summary, Example 1 demonstrates a good overall balance among reflectivity, weather resistance retention, hydrophobicity, interlayer bonding performance, and puncture-resistant self-healing waterproofing performance, and can be considered a preferred embodiment. Example 2 verifies that significantly better overall performance than ordinary TPO rolls can still be achieved with lower formulation ratios and lower process parameters. Example 3 verifies that reflectivity, heat insulation, and self-healing capabilities can be further improved with higher formulation ratios and higher process parameters. Comparative Examples 1, 2, and 3 respectively demonstrate the contribution of the key technical features of this invention to the overall performance from three aspects: the high-reflectivity weather-resistant layer, the self-healing sealing layer, and the traditional aluminum foil reflective structure.
[0106] Test and Evaluation Methods Total solar reflectance and diffuse reflection ratio: Each sample was placed at 23±2℃ and 50±5% relative humidity for 24 h. The total reflectance and diffuse reflection components were measured under the same incident conditions. Five locations were randomly selected from each sample, and the average value was taken. The diffuse reflection ratio was calculated as "diffuse reflectance / total reflectance × 100%". A higher total reflectance indicates stronger overall solar reflectance, and a higher diffuse reflection ratio indicates a more uniform distribution of reflected light direction.
[0107] Comprehensive aging and thermal cycling evaluation: Each sample underwent 1000 hours of comprehensive aging, and the total solar reflectance was measured under the same conditions before and after aging to calculate the reflectance retention rate; in addition, 100 cycles of thermal cycling from -20℃ to 80℃ were performed to observe whether cracks, wrinkles, bulges or delamination appeared on the sample surface and between layers, in order to evaluate the long-term weather resistance stability of the reflective structure and the multilayer composite structure.
[0108] Evaluation of water contact angle and thermal conductivity: Deionized water was dropped onto the surface of the high-reflectivity weather-resistant layer, and five locations were randomly tested and the average contact angle was taken. The larger the contact angle, the better the hydrophobic self-cleaning performance. The steady-state thermal conductivity of the samples of the same thickness was tested under stable temperature conditions. The lower the thermal conductivity, the better the thermal insulation and barrier performance.
[0109] Interlayer peeling and puncture waterproofing evaluation: The specimens were cut into strips with a width of 25 mm, and peeled 180° at a constant speed, with the average peeling force recorded during the stable phase. For puncture water tightness testing, photovoltaic bracket fasteners of the same specifications were used to vertically puncture the specimens, and the specimens were kept under a water pressure of 0.30 MPa for 2 hours. The appearance of water droplets or continuous seepage on the back side and around the fasteners was observed. After the fasteners were removed, the specimens were placed at room temperature for 24 hours and at 60°C for 2 hours, respectively, and then kept under a water pressure of 0.20 MPa for 2 hours to evaluate the backfilling and heat-promoted self-healing sealing ability of the puncture holes.
[0110] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of the present invention.
Claims
1. A high-reflectivity TPO waterproof membrane for photovoltaic applications, characterized in that, include: The layers are sequentially composited from top to bottom: a high-reflectivity weather-resistant layer, a transition adhesive layer, an intermediate functional layer, a self-healing sealing layer, and a bottom reinforcement layer. The high-reflectivity weather-resistant layer is used to reflect and scatter sunlight incident on the photovoltaic module installation area, and includes a TPO matrix and high-refractive-index hollow reflective particles and hollow scattering particles dispersed in the TPO matrix. The transition bonding layer is used to connect the high-reflectivity weather-resistant layer and the intermediate functional layer and to relieve interlayer thermal stress; The intermediate functional layer, which provides mechanical support and thermal insulation, includes a TPO matrix and hollow fillers dispersed in the TPO matrix; The self-healing sealing layer is disposed between the intermediate functional layer and the bottom reinforcement layer, and is used to provide flow sealing for roll material ruptures caused by external mechanical punctures. The self-healing sealing layer includes a TPO matrix, liquid polyisobutylene, and tackifying resin. The bottom reinforcement layer is used to connect with the target attachment base layer.
2. The waterproof membrane according to claim 1, characterized in that, The high-reflectivity weather-resistant layer comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of high-refractive-index hollow reflective particles, 5 to 15 parts of hollow scattering particles, 0.5 to 2 parts of ultraviolet absorber, 0.3 to 1 part of antioxidant, and 0.2 to 0.5 parts of light stabilizer. The high-refractive-index hollow reflective particles are titanium dioxide hollow particles or titanium dioxide-coated hollow particles, and the hollow scattering particles are hollow glass microspheres.
3. The waterproof membrane according to claim 2, characterized in that, The high-refractive-index hollow reflective particles have a particle size D50 of 2μm to 8μm and a hollowness greater than 85%. The particle size D50 of the hollow scattering particles is 10μm to 50μm; The high-refractive-index hollow reflective particles fill the packing gaps between the hollow scattering particles to form a multi-scale graded reflective structure within the high-reflectivity weather-resistant layer.
4. The waterproof membrane according to claim 3, characterized in that, The surface of the high-reflectivity weather-resistant layer away from the transition adhesive layer has a micro-nano rough structure, which includes micron-sized protrusions and nano-sized pits formed between or on the surface of the micron-sized protrusions. The diameter of the micron-sized protrusion is 5μm to 20μm, the height is 3μm to 10μm, and the depth of the nano-sized pit is 0.5μm to 2μm.
5. The waterproof membrane according to claim 4, characterized in that, The self-healing sealing layer comprises, by weight, 100 parts of TPO matrix, 15 to 30 parts of liquid polyisobutylene, 5 to 15 parts of tackifying resin, and 3 to 8 parts of microcapsule wax. The liquid polyisobutylene has a molecular weight of 1000-3000, and the microcapsule wax has a phase transition temperature of 50℃-70℃.
6. The waterproof membrane according to claim 5, characterized in that, The intermediate functional layer comprises, by weight, 100 parts of TPO matrix, 20 to 40 parts of hollow filler, 10 to 20 parts of inorganic filler, and 3 to 8 parts of processing aid; The hollow filler is hollow glass microspheres, the inorganic filler is calcium carbonate, and a closed-cell structure is formed in the intermediate functional layer to reduce the thermal conductivity of the waterproof membrane and improve its mechanical support performance. The transition adhesive layer comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of maleic anhydride grafted polyolefin, and 5 to 15 parts of tackifying resin. The bottom reinforcing layer comprises, by weight, 100 parts of TPO matrix, 10 to 25 parts of sheet-like reflective filler, and 5 to 10 parts of tackifying resin; The sheet-like reflective filler is dispersed in the TPO matrix of the bottom reinforcing layer, and the sheet-like reflective filler is titanium dioxide coated mica sheet.
7. A method for preparing the high-reflectivity TPO waterproof membrane for photovoltaic applications according to any one of claims 1-6, characterized in that, include: Step S1: Obtain the raw materials for the high-reflectivity weather-resistant layer, the transition adhesive layer, the intermediate functional layer, the self-healing sealing layer, and the bottom reinforcement layer, respectively. Step S2: The high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material and bottom reinforcement layer material are melted and plasticized respectively; Step S3: The melted and plasticized materials are compositely formed by a multi-layer co-extrusion device to form a five-layer composite roll material from top to bottom, including a high-reflectivity weather-resistant layer, a transition bonding layer, an intermediate functional layer, a self-healing sealing layer and a bottom reinforcement layer. Step S4: Perform surface structure treatment on the side of the high-reflectivity weather-resistant layer away from the transition bonding layer to form a micro-nano rough structure on the surface of the high-reflectivity weather-resistant layer for diffuse reflection and hydrophobic self-cleaning. Step S5 involves cooling, shaping, traction, edge trimming, and winding of the five-layer composite roll with the micro-nano rough structure to obtain the photovoltaic high-reflectivity TPO waterproof roll.
8. The preparation method according to claim 7, characterized in that, In step S4, the surface structure treatment performed on the side of the high-reflectivity weather-resistant layer away from the transition adhesive layer includes: The surface of the high-reflectivity weather-resistant layer is subjected to plasma treatment, embossing treatment, and hydrophobic treatment in sequence; The plasma treatment uses a mixed atmosphere of oxygen and argon, with a treatment power of 200W to 500W and a treatment time of 2 to 5 minutes. The embossing process uses an embossing roller with a hydrophobic microstructure on its surface, with an embossing temperature of 80℃~120℃ and an embossing pressure of 2MPa~5MPa, to form a micro-nano rough structure including micron-level protrusions and nano-level pits on the surface of the high-reflectivity weather-resistant layer. The hydrophobic treatment involves spraying or impregnating the micro / nano rough structure with a fluorosilane solution to form a hydrophobic surface layer on the surface of the micro / nano rough structure.
9. The preparation method according to claim 7, characterized in that, In step S3, the melted and plasticized high-reflectivity weather-resistant layer material, transition adhesive layer material, intermediate functional layer material, self-healing sealing layer material and bottom reinforcement layer material are compositely formed by a five-layer co-extrusion distributor. The extrusion temperature of each layer of material is set to 180℃~240℃, the cooling roller temperature is 30℃~50℃, and the traction speed is 5m / min~20m / min; Adjust the extrusion amount of each extrusion mechanism so that the thickness of the high-reflectivity weather-resistant layer is 0.5mm to 1.0mm, the thickness of the transition bonding layer is 0.2mm to 0.4mm, the thickness of the intermediate functional layer is 1.0mm to 2.0mm, the thickness of the self-healing sealing layer is 0.3mm to 0.6mm, and the thickness of the bottom reinforcing layer is 0.5mm to 1.0mm.
10. The preparation method according to claim 8, characterized in that, The width of at least one side of the self-healing sealing layer is smaller than that of the bottom reinforcement layer, so that the lower surface of at least a portion of the intermediate functional layer on the corresponding side is connected to the upper surface of the bottom reinforcement layer; In the plasma treatment, the volume ratio of oxygen to argon is 1:4 to 1:1.
Citation Information
Patent Citations
Polyolefin waterproof coiled material and preparation and application thereof
CN117922135A